Cost-effective bi-functional resin reinforced with a nano-inclusion blend for vat photopolymerization additive manufacturing: The effect of multiple antibacterial nanoparticle agents - Nectarios Vidakis; Markos Petousis; Amalia Moutsopoulou; Nikolaos Mountakis; Sotirios Grammatikos; Vassilis Papadakis; Dimitris Tsikritzis (Biomedical Engineering Advances, 2023)
Herein, a blend of nanoparticle (NP) inclusions has been arranged at various loadings into a photosensitive resin, while bi-functional three-dimensional (3D) printed specimens were fabricated through a vat photopolymerization process, to elucidate physicochemical mechanisms and synergistic effects, over the filler loading. Energy-dispersive X-ray spectroscopy (EDS), Raman, and thermogravimetric analysis (TGA) revealed the chemical/spectroscopic and thermal properties of the fabricated specimens. Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) depicted the surface morphology, while SEM fractography demonstrated the morphology of tensile test specimens’ fractured surfaces. Mechanical tests exhibited a strong reinforcement mechanism. The highest reinforcement of 20.8% in the tensile strength is reported for the 2 wt.% nanocomposite. All the prepared recipes exhibited a boosted antibacterial performance, as was documented via a screening agar well diffusion method. The research herein leads towards a novel generation of low-cost bi-functional materials for 3D printing bioactive applications, where mechanical reinforcement and antibacterial performance are required in the operational environment.